Water Erosion in the Donga Soils in Subhumid Zone in West Africa - AVAKOUDJO, JULIEN; KOUELO ALLADASSI, FÉLIX; KINDOMIHOU, M. VALENTIN; AKPONIKPE, Pierre Irénikatché; AZONTONDE, ANASTASE; SINSIN, AUGUSTIN BRICE; AKPLO, Tobi Moriaque; Agonvinon, Mahugnon Socrate (My University, 2020)
The runoff and soil loss were assessed in situ at the scale of 2.12 m2 plots during the rainy season of 2010 to better understand the determinants and magnitude of the massive soil loss and land subsidence (donga) in the sub-humid zone of Africa in Karimama, North Benin. The experimental design was a split plot with two factors: the topography in 3 modalities (upstream, center and downstream of the donga) was assigned as main plot factor and the degree of degradation of dongas in 2 modalities (beginner dongas and advanced dongas) was assigned as subplot factor. Runoff water was collected through a storage system composed of two tanks. Data were collected on 36 plots (9 plots per donga × 4 dongas). The runoff varies significantly from one site to another for the rainy episode of October 10, 2010. It is twice as high in land use areas (5.87 mm) as in W Park (2.32 mm; l.s.d. = 1.81 mm). From upstream to downstream, runoff and soil loss increased from 2.4 mm to 85.3 mm and 80 g∙m−2 to 197 g∙m−2, respectively. Runoff is high in the early dongas (7.60 mm) and low in the advanced dongas (5.68 mm) in contrast to lower soil loss in the early dongas (34 g∙m−2) and high in the advanced dongas (237 g∙m−2). The low value of soil loss with respect to the magnitude of the phenomenon suggests the probable occurrence of other soil loss mechanisms to be elucidated.
Keywords: W National Park; Land Use Areas; Dongas; Runoff; Erosion; Soil Loss